Telescoping the Synthesis of the [18F]CABS13 Alzheimer's Disease Radiopharmaceutical via Flow Microfluidic Rhenium(I) Complexations. Issue 37 (24th September 2020) - Klenner, Mitchell A.; Fraser, Benjamin H.; Moon, Vaughan; Evans, Brendan J.; Massi, Massimiliano; Pascali, Giancarlo
Abstract : The syntheses of rhenium(I) complexes were achieved under flow microfluidic conditions. The use of a single microreactor was applied towards complexation of the 6‐chloro‐2, 2'‐bipyridine diimine ligand, with ideal complexation conditions around 170 °C. Subsequent radiolabelling with [ 18 F]fluoride was further achieved by flowing through a second heated microreactor, alongside a stream of dried radiofluorination media. Temperature modulation across both microreactors resulted in 23.6 % and 37.0 % radiochemical yield (RCY) of [ 18 F]6‐fluoro‐2, 2'‐bipyridine and its associated [ 18 F]tricarbonyl(2‐fluoro‐2, 2'‐bipyridine)rhenium(I) chloride complex, respectively. Translation of this set‐up to the synthesis of the [ 18 F]CABS13 Alzheimer's disease positron emission tomography (PET) imaging agent was achieved with the incorporation of a third microreactor to enable thermal control of the complexation, fluorination and decomplexation pathways. Optimal RCYs of 2.7 % and 1.9 % of [ 18 F]CABS13 and its rhenium(I) complexation were achieved in‐flow, respectively. However, discrepancies in the RCYs were found to arise from differences in the grade of anhydrous dimethyl sulfoxide (DMSO) employed in the continuous‐flow reactions. Anhydrous DMSO from Sigma‐Aldrich (≤ 99.9 %) in former experiments afforded higher yielders in comparison to replicate experiments employing anhydrous DMSO from Merck Millipore (≤ 99.7 %), thus demonstrating that control of the solvent grade is key to optimizing reaction RCYs. Abstract : Telescoped synthesis of the [ 18 F]CABS13 radiopharmaceutical, used in the PET imaging of Aβ plaques characteristic of Alzheimer's disease, by an in‐flow telescoped rhenium(I) complexation‐dissociation approach is reported.